Altered Expression of the Hedgehog Pathway Proteins BMP2, BMP4, SHH, and IHH Involved in Knee Cartilage Damage of Patients With Osteoarthritis and Kashin-Beck Disease. (March 2022) - Deng, Huan; Xiao, Xiang; Chilufya, Mumba Mulutula; Qiao, Lichun; Lv, Yizhen; Guo, Ziwei; Lei, Jian; Liu, Jiaxin; Zhao, Yan; Zhang, Jiaheng; Wang, Wenyue; Han, Jing; et al.
Objective: To investigate the expression of Hedgehog (HH) signaling pathway proteins in knee articular cartilage from Kashin-Beck disease (KBD) and osteoarthritis (OA) patients. Methods: Knee articular cartilage samples were collected from normal (N), OA, and KBD adults (aged 38-60 years) and divided into 3 groups with 6 subjects in each group. The localization of the HH pathway proteins bone morphogenetic protein 2 (BMP2), bone morphogenetic protein 4 (BMP4), Sonic hedgehog (SHH), and Indian hedgehog (IHH) was observed with the microscope after immunohistochemical (IHC) staining. Positive staining cell rates of each proteins were compared. Results: The strongest stainings of all proteins were observed in the middle zones of all 3 groups. The positive staining rates of BMP4 and IHH were significantly lower in the OA and KBD groups than those in the N group in all 3 zones. The positive staining rates of BMP2 and SHH tend to be lower in the OA and KBD groups than those in the N group in the deep zone, while higher in the OA and KBD groups than those in the N group in superficial and middle zones. Conclusions: Altered expression of the HH pathway proteins BMP2, BMP4, SHH, and IHH was found in OA and KBD articular cartilage. There seemed to be a compensatory effect between SHH and IHH in cartilage damage. Further studies on the pathogenesis of OA and KBD may be carried out from these aspects in the future.